Analysis of Decision Process to Buy Free-Range Eggs and the Implication on Marketing Mix (A Case Study to Wholesalers and Retailers Consumers in Traditional Markets in Purworejo District) - Zulfanita Zulfanita; Roisu Eny Mudawaroch; Jeki Mediantari Wahyu Wibawanti (ANIMAL PRODUCTION, 2020)
This research aimed to compare the characteristics of free-range eggs consumers, to analyse their buying decision process and consumer satisfaction level, and to formulate the implication on free-range marketing mix across wholesalers and retailers in Purworejo districts. The research sample was 32 respondents, consisted of 16 wholesalers and 16 retailers selected with purposive sampling because of the limited number of respondents in each sub-district. The consumers were selected through snowball sampling from one respondent to another. The parameters included the general characteristics, the decision to buy free-range eggs, consumers’ satisfaction level, and marketing mix implications. The Data were analysed descriptively using Chi-Square, Mann-Whitney Customer Satisfaction Index (CSI), and Importance and Performance Analysis (IPA). The result found different characteristics across consumers of free-range eggs in both wholesalers and retailers regarding age group, marital status, education background, gender, occupation, and geographic locations. The different process of buying decision making was due to need identification. Regarding gathering information, the wholesaler consumers relied on electronic media and their neighbours, whereas the retailer consumers only from their neighbours. The main consideration to purchase free-range eggs among wholesaler consumers was the cleanliness of eggs, whereas the retailer consumers were the cleanliness and price of eggs. The consumer satisfaction index on consumers in wholesalers and retailers was 65.16 and 68.82, respectively, indicative of the satisfied category. The marketing mix implication on both sellers was improving the cleanliness of free-range eggs and the market area, matching selling price with the market price, controlling the quality of free-range eggs from the suppliers, and revisiting the supply system to ensure the real-time availability of free-range eggs.